Morphology of boulder-bed semi-alluvial channel beds: a flume study modelling streams in northern Fennoscandia ... : Morfologi av blockiga semialluviala vattendrag: experimentell strömränna-studie för att modellera vattendrag i norra Fennoskandia ... - Polvi, Lina (Umeå University, 2020)
In northern Fennoscandia, semi-alluvial boulder-bed channels with coarse glacial legacy sediment are abundant and due to widespread anthropogenic manipulation during timber-floating, unimpacted reference reaches are rare. The landscape context of these semi-alluvial rapids— with numerous mainstem lakes that buffer high flows and sediment connectivity in addition to low sediment yield— contribute to low amounts of fine sediment and incompetent flows to transport boulders. To determine the morphodynamics of semi-alluvial rapids and potential self-organization of sediment with multiple high flows, a flume experiment was designed and carried out to mimic conditions in semi-alluvial rapids in northern Fennoscandia. Two slope setups (2% and 5%) were used to model a range of flows (Q1, Q2, Q10 & Q50) in a 8 x 1.1 m flume with a sediment distribution analogous to field conditions; bed topography was measured using structure-from-motion photogrammetry (SfM) after each flow to obtain digital elevation models ... : I norra Fennoskandia är det vanligt med blockiga semialluviala vattendrag med grov glacialsediment. För att få en bättre förståelse om hur dessa vattendrag formas utfördes ett experiment i en strömränna med liknande förhållanden som dessa semialluviala forsar. Två lutningar användes, 2% och 5% med fem olika flöden i (Q1, Q2, Q10 & Q50) i en ränna som var 8 x 1.1 m med kornsorleksfördelning som liknande fältförhållanden. Fårans morfologi mättes med structure-from-motion photogrammetry (SfM) efter varje flöde för att skapa höjdmodeller (s.k. DEMs). Höjdmodellerna har en upplösning på 5 x 5 mm och visar utgångsförhållande samt efter varje flöde kördes. Det finns också shapefiler av digitaliserade sedimentkorn som är större än D84 som skapades baserat på utgångsförhållanden. Resultat från analyser baset på dessa höjdmodeller har konsekvenser för hur man bör restaurera lekbottnar för lax och öring i norra Fennoskandia samt betonar vikten av att förstå hur block påverkar vattendrags morfodynamik. Se också den ...